POSITIVE CLASSROOM INTERACTION IN ESP TEACHING - Tonenchuk, Tetiana (My University, 2026)
The purpose of this article is to analyze strategies for building positive interaction in ESP, determine the influence of the emotional climate and rapport on learning outcomes, and justify the role of a student-centered approach in creating a goal-oriented educational environment.
Keywords: Classroom Interaction; ESP